2018
DOI: 10.2343/geochemj.2.0496
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of desorption ratios of radio/stable caesium from environmental samples (aerosols and soils) leached with seawater, diluted seawater and ultrapure water

Abstract: rest of the released 137 Cs went out to the ocean. The radioactive aerosols were scavenged from the atmosphere to the ocean surface by dry and wet depositions, with the result that the deposition has increased the concentration of radio Cs in the surface seawater extensively (Aoyama et al., 2016; Kaeriyama, 2016; and references therein). Although radio Cs was in the uppermost surface layer and existed predominantly as dissolved species shortly after the FDNPP accident (e.g., Buesseler et al., 2012; Honda et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[13][14][15][16] The estuary environment is important for the desorption of Cs from soil, sediments and suspended solids by freshwater-seawater. Sakaguchi et al 17 showed that more than 15% of total 137 Cs in the surface soil sample was desorbed by seawater leaching. Takata et al 18 reported that 0.75 to 6.6% of 137 Cs were desorbed from the sieved particles (<74 μm) of the riverbank soils and river-bottom sediments from four rivers in Fukushima, Ibaraki and Chiba Prefecture by using filtered natural seawater.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The estuary environment is important for the desorption of Cs from soil, sediments and suspended solids by freshwater-seawater. Sakaguchi et al 17 showed that more than 15% of total 137 Cs in the surface soil sample was desorbed by seawater leaching. Takata et al 18 reported that 0.75 to 6.6% of 137 Cs were desorbed from the sieved particles (<74 μm) of the riverbank soils and river-bottom sediments from four rivers in Fukushima, Ibaraki and Chiba Prefecture by using filtered natural seawater.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the contribution of 137 Cs added via desorption (i.e., the fraction of Cs that could be desorbed from riverine suspended particles), which is dependent on two parameters: the fraction of desorption and the amount of 137 Cs in suspended particles. The fraction of 137 Cs that desorbs from particles (0.03–0.3) has been estimated experimentally using samples relevant to the FDNPP accident. The wide range of this fraction is presumably due to differences in the composition of the particles and on sorption sites . Although particles containing on the order of 10 Bq/kg-dry of 137 Cs have been shown to contribute very little to the increase in dissolved 137 Cs (e.g., the Tone River), particles in this study contained high activities of 137 Cs of 170–5500 Bq/kg-dry.…”
Section: Resultsmentioning
confidence: 81%
“…In general, the reduction of K d from rivers to the nearshore zone was due mainly to the release of Cs from suspended particulate matter in response to salinity changes during estuarine mixing and not just to the change and/or difference in the chemical composition of suspended particles from rivers to coastal areas. [24][25][26][27]30,32,43 It has been reported that in the Danube−Black Sea mixing zone 19 and in the southern Baltic Sea, 44 the total (particulate plus dissolved phase) 137 Cs activity increases continuously from rivers to marine waters, but the fraction of particulate 137 Cs decreases as salinity increases.…”
Section: Distribution Coefficient (K D )mentioning
confidence: 99%
See 1 more Smart Citation